The nuclear envelope in genome organization, expression and stability - Mekhail, Karim (2010)
Non-random positioning of chromosomal domains relative to each other and to nuclear landmarks is a common feature of eukaryotic genomes. In particular, the distribution of DNA loci relative to the nuclear periphery has been linked to both transcriptional activation and repression. Nuclear pores and other integral membrane protein complexes are key players in the dynamic organization of the genome in the nucleus, and recent advances in our understanding of the molecular networks that organize genomes at the nuclear periphery point to a further role for non-random locus positioning in DNA repair, recombination and stability.